2019
DOI: 10.1111/jfb.14101
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment dynamics and fishery characteristics of juvenile goatfishes Mulloidichthys spp. in Hawai‘i

Abstract: The most common goatfishes in Hawai‘i, Mulloidichthys flavolineatus and M. vanicolensis, comprise a unique resource due to their cultural, ecological and biological significance. These species exhibit pulse‐type recruitment to nearshore areas during the summer months. Such pulses of juvenile fishes provide prey for pelagic and nearshore fishes and support a popular directed fishery. However, limited scientific information exists on juvenile stages of these fishes, known locally as oama, despite their contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Because M. vanicolensis is widely distributed in the Indo‐Pacific and has a very long pelagic larval phase of more than 2 months (Kamikawa et al ., 2019), genetic continuity between regions has been of interest for some time. Stepien et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because M. vanicolensis is widely distributed in the Indo‐Pacific and has a very long pelagic larval phase of more than 2 months (Kamikawa et al ., 2019), genetic continuity between regions has been of interest for some time. Stepien et al .…”
Section: Discussionmentioning
confidence: 99%
“…Because M. vanicolensis is widely distributed in the Indo-Pacific and has a very long pelagic larval phase of more than 2 months (Kamikawa et al, 2019), genetic continuity between regions has been of interest for some time. Stepien et al (1994) analysed allozymes and showed that there are restrictions on gene flow and differences in gill-raker counts and body colour between the Indian Ocean and Pacific populations.…”
Section: Life-history Traitsmentioning
confidence: 99%